Effect of Nanometal Additives on The Ignition of Al -Based Energetic Materials; Nano and Micro‐Scale Energetic Materials: Propellants and Explosives - Korotkikh A. G. Aleksandr Gennadievich; Sorokin I. V. Ivan Viktorovich; Zarko V. E. Vladimir Egorovich; Arkhipov V. A. Vladimir Afanasjevich (2023, 2023)
Study related to the use of metal fuels in energetic material is aimed at reducing agglomeration, the negative effect of the oxide cover on the surface of particles, and increasing the completeness of combustion of the active metal (mainly aluminum) in composite solid propellants with the addition of combustion catalysts or the application of a protective layer on metal particles. The practical use of boron powder is complicated by high ignition time and incomplete combustion. To improve the ignition characteristics of boron, various additives in the form of metals or their oxides (Mg, Al, Fe, Cu, Bi, Ce) are used, which reduce the ignition time and temperature of boron particles. Promising metal fuels for energetic materials are metal compounds such as metal/nonmetal, metal/metal alloys, as well as mechanical mixtures of metal powders. The chapter presents the results of an experimental study of the ignition characteristics of energetic materials, containing nanopowders of Al/B, Al/Fe, Al/Ti, and Al/Cu. On the basis of experimental data, the activation energy and the multiplication of the heat effect of the reaction and the pre-exponent were calculated. A change in the component composition of a bimetal fuel makes it possible to significantly modify the ignition characteristics of the energetic material.